2012
DOI: 10.1371/journal.pone.0033372
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Aggregation Behavior of a Non-Amyloidogenic λ Light Chain Dimer Deriving from U266 Multiple Myeloma Cells

Abstract: Excessive production of monoclonal light chains due to multiple myeloma can induce aggregation-related disorders, such as light chain amyloidosis (AL) and light chain deposition diseases (LCDD). In this work, we produce a non-amyloidogenic IgE λ light chain dimer from human mammalian cells U266, which originated from a patient suffering from multiple myeloma, and we investigate the effect of several physicochemical parameters on the in vitro stability of this protein. The dimer is stable in physiological condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
6
14
0
Order By: Relevance
“…Whereas the denaturation of most LC was reversible, all -MM LC denatured irreversibly after heating. We found that -and -isotype LC had different stabilities in thermal denaturation, with an average T m of 53 Ϯ 5 and 59 Ϯ 2°C, respectively, which corresponds to previously published data (28,30,44,64). We did not find strong systematic differences in stability between AL-and MM-LC.…”
Section: Discussionsupporting
confidence: 89%
“…Whereas the denaturation of most LC was reversible, all -MM LC denatured irreversibly after heating. We found that -and -isotype LC had different stabilities in thermal denaturation, with an average T m of 53 Ϯ 5 and 59 Ϯ 2°C, respectively, which corresponds to previously published data (28,30,44,64). We did not find strong systematic differences in stability between AL-and MM-LC.…”
Section: Discussionsupporting
confidence: 89%
“…This has been seen several times before, especially for the amorphous aggregation of immunoglobulin-like domains. 12,20,32,39 The fact that I27 aggregation occurs from a specific, TFE-induced structure is reminiscent of recent work on the p53 core domain, which demonstrated that aggregation from the apoprotein is substantially faster than aggregation from the holo-protein. 40 It also agrees with observations that the stabilization of partly folded intermediate states causes increased aggregation in proteins such as transthyretin (TTR) and lysozyme.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the divalency of the anion confers peculiar properties in terms of charge screening, anion binding, and salt bridge formation. The overimposition of the different electrostatic effects can either promote (34)(35)(36) or inhibit (37) the protein aggregation propensity. In the case of an IgG2 monoclonal antibody, we have recently reported a maximum of the aggregation propensity as a function of sulfate concentration (22).…”
Section: Introductionmentioning
confidence: 99%